Analytical methods for energy diversity and security : portfolio optimization in the energy sector : a tribute to the work of Dr. Shimon Awerbuch - Awerbuch, Shimon; Bazilian, Morgan; Roques, Fabien A. (Elsevier global energy policy and economics series, 2008)
This is an ideal volume for professionals in academia, industry and government interested in the rapidly evolving area at the nexus between energy and climate change policy. The cutting-edge international contributions allow for a wide coverage of the topic. Energy Diversity and Security focuses on the consideration of financial risk in the energy sector. It describes how tools borrowed from financial economic theory, in particular mean-variance portfolio theory, can provide insights on the costs and benefits of diversity, and thus inform investment decision making in conditions of uncertainty. It gives the reader an in-depth understanding of how to manage risk at a time when the world's focus is on this area. The book provides insights from leading authorities in the area of energy security. It gives readers abundant, rigorous analysis and guidance at a critical time in facing the twin challenges of energy security and climate change. The book also highlights the role of clean energy technology in moving towards future diverse and intelligent electricity systems. It will be a trusted, first point of reference for decision-makers in the field of energy policy. The book includes a foreword by the 2007 Nobel Peace Prize winner. All royalties from sale of this book will be donated to charities working in the energy sector in the developing world. . Theoretical underpinning and applied use of Portfolio theory in the energy sector . In-depth consideration of risk . Contributions from leading international energy economists . Innovative methodologies for thinking about energy security and diversity.